Functional Division Between the RecA1 and RecA2 Proteins in Myxococcus xanthus - Sheng, Duo-Hong; Wang, Yi-Xue; Qiu, Miao; Zhao, Jin-Yi; Yue, Xin-Jing; Li, Yue-Zhong (Frontiers in Microbiology, 2020)
Myxococcus xanthus DK1622 has two RecA genes, recA1 (MXAN_1441) and recA2 (MXAN_1388), with unknown functional differentiation. Herein, we showed that both recA genes were induced by ultraviolet (UV) irradiation but that the induction of recA1 was more delayed than that of recA2. Deletion of recA1 did not affect the growth but significantly decreased the UV-radiation survival, homologous recombination (HR) ability, and induction of LexA-dependent SOS genes. In contrast, the deletion of recA2 markedly prolonged the lag phase of bacterial growth and increased the sensitivity to DNA damage caused by hydrogen peroxide but did not change the UV-radiation resistance or SOS gene inducibility. Protein activity analysis demonstrated that RecA1, but not RecA2, catalyzed DNA strand exchange (DSE) and LexA autocleavage in vitro. Transcriptomic analysis indicated that RecA2 has evolved mainly to regulate gene expression for cellular transportation and antioxidation. This is the first report of functional divergence of duplicated bacterial recA genes. The results highlight the evolutionary strategy of M. xanthus cells for DNA HR and genome sophistication.